Načela medicinske etike in etične dileme v fiziatrični ambulanti - Ferjančič, Marjeta (Rehabilitacija (Ljubljana), 2017)
Ethics and ethical issues are a part of all aspects of life and medicine. Medical ethics is based on medical knowledge and moral principles. Respect of ethical principles is the basis of any medical intervention. The main ethical principles are: beneficience, nonmaleficience, autonomy, justice, truthfulness and confidentiality. Ethical issues in the physical medicine and rehabilitation settings are common and health care professionals face a range of ethical challenges. In a physiatric clinic, we are confronted with the fact that the options for doing what is best for the patient are often limited by external factors, including rules and regulations of the health care system and the associated payment system.
Keywords: ethical issues; Ethics; etične dileme; fiziatrična ambulanta; fizikalna terapija; medical ethics; medicinska etika; physiatric clinic; physical therapy; rehabilitacijska medicina; Rehabilitation; rehabilitation medicine